2019
DOI: 10.3329/bjms.v18i3.41620
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Conventional Methods and Automated Systems for Determining Antibiotic Susceptibility of Bacteria Isolated from Urine Culture

Abstract: Objective: The aim of our study was to compare the results obtained from different methods, which are used to determine the susceptibility to antimicrobials, and to determine the agreement between them. Materials and Methods: A total of 397 strains consisting of 329 gram negative and 68 gram positive bacteria that were isolated from urine samples and identification and antibiogram of which were performed by automated systems, were included in the study. The results obtained from broth microdilution, E te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This rate is higher, especially for ertapenem [23]. In a study which comparing the antibiotic susceptibility of bacteria isolated from urine culture with conventional methods and automated systems has shown that agreement for E-test was 95.3% with a very major error rate of 1.1 [24]. In a study comparing meropenem MICs and susceptibility with various tests in Carbapenem-resistant K. pneumonia strains; E-test demonstrated 82.6% agreement with broth microdilution MICs, a very major error rate of 2.2%, and a minor error rate of 2.2% and Vitek 2 automated system MIC agreement was 30.4%, with a 23.9% very major error rate and a 39.1% minor error rate [25].…”
Section: Discussionmentioning
confidence: 99%
“…This rate is higher, especially for ertapenem [23]. In a study which comparing the antibiotic susceptibility of bacteria isolated from urine culture with conventional methods and automated systems has shown that agreement for E-test was 95.3% with a very major error rate of 1.1 [24]. In a study comparing meropenem MICs and susceptibility with various tests in Carbapenem-resistant K. pneumonia strains; E-test demonstrated 82.6% agreement with broth microdilution MICs, a very major error rate of 2.2%, and a minor error rate of 2.2% and Vitek 2 automated system MIC agreement was 30.4%, with a 23.9% very major error rate and a 39.1% minor error rate [25].…”
Section: Discussionmentioning
confidence: 99%
“…The turbidity of the sample was measured by a UV−Vis spectrophotometer at the 550-nm wavelength. The bacterial suspension was diluted to obtain a reading of 0.125, equivalent to 0.5 McFarland turbidity [ 39 ]. Antibacterial activities of the coatings and of each primary component were evaluated using the well diffusion method.…”
Section: Methodsmentioning
confidence: 99%
“…A study showed disk diffusion method, compared to automated systems, had significant efficiency in determination of antibiotic susceptibility of gram-negative and gram-positive bacteria. 23 For Gram-negative bacteria 19 different types of antibiotics from 9 classes were cast-off for the study: β-lactamases (Ampicillin-10 µg, Aztreonam-30 µg, Amoxicillin-Clavulanic acid-30 µg, Amoxicillin-30 µg), Carbapenem (Imepenem-10 µg, Meropenem-10 µg), Aminoglycosides (Streptomycin-10 µg, Kanamycin-5 µg, Gentamycin-10 µg, Amikacin-30 µg), Fluroquinolone (Levofloxacin-5 µg, Ciprofloxacin-5 µg), Phenicol (Chloramphenicol-30 µg), Tetracycline (Tetracycline-30 µg), Cotrimoxazole (Co-trimoxazole-25 µg), Cephalosporin (Cefepime-30 µg, ceftazidime-30 µg, Cefotaxime-30 µg), Macrolid (Azithromycin-10 µg) whereas for Gram-positive bacteria 18 different types of antibiotics from 8 classes were selected for the study: β-lactamases (Penicillin-10 µg, Ampicillin-10 µg, Oxacillin-30 µg, Amoxicillin-Clavulanic acid-30 µg), Carbapenem (Imepenem-10 µg, Meropenem-10 µg), Aminoglycosides (Gentamycin-10 µg), Fluroquinolone (Levofloxacin-5 µg, Norfloxacin-10 µg, Ciprofloxacin-5 µg), Cephalosporin (Cefotaxime-30 µg, Cefepime-30 µg, ceftazidime-30 µg), Tetracycline (Tetracycline-30 µg), Macrolid (Erythromycine-15 µg, Lincomycin-2 µg, Clindamycin-2 µg), Phenicol (Chloramphenicol-30 µg) against gram positive Staphylococcus spp.. Mueller-Hinton agar plate was used for antimicrobial susceptibility test (AST) and incubated at 37˚C for 18-24 hours and measured the inhibition zone diameters (IZDs). The IZDs were recorded according to the CLSI standard antibiotic breakpoints and interpreted as susceptible, intermediate and resistant.…”
Section: Antimicrobial Susceptibility Test (Ast)mentioning
confidence: 99%